Medical management of risk factors for vascular disease. Issue 5 (May 2021) - Rasiah, Michael Greshan; Modarai, Bijan
Abstract: Peripheral arterial disease (PAD) is a powerful marker of the risk of cardiovascular events such as stroke and myocardial infarction, even in asymptomatic patients. The development of PAD is underpinned by both modifiable risk factors (including smoking, diabetes, dyslipidaemia, hypertension and obesity) and non-modifiable risk factors (including male gender and increased age). Optimizing medical management of risk factors–with tight control of diabetes, antiplatelet therapy and exercise–can significantly reduce the risk of cardiovascular morbidity and mortality.